Biological Properties of Tocotrienols: Evidence in Human Studies - Meganathan, Puvaneswari (Int J Mol Sci, 2016)
Vitamin E has been recognized as an essential vitamin since their discovery in 1922. Although the functions of tocopherols are well established, tocotrienols have been the unsung heroes of vitamin E. Due to their structural differences, tocotrienols were reported to exert distinctive properties compared to tocopherols. While most vegetable oils contain higher amount of tocopherols, tocotrienols were found abundantly in palm oil. Nature has made palm vitamin E to contain up to 70% of total tocotrienols, among which alpha-, gamma- and delta-tocotrienols are the major constituents. Recent advancements have shown their biological properties in conferring protection against cancer, cardiovascular diseases, neurodegeneration, oxidative stress and immune regulation. Preclinical results of these physiological functions were translated into clinical trials gaining global attention. This review will discuss in detail the evidence in human studies to date in terms of efficacy, population, disease state and bioavailability. The review will serve as a platform to pave the future direction for tocotrienols in clinical settings.